Does Self-Regulated Learning Mediate the Effect of Smartphone Addiction on Academic Procrastination? A SEM Analysis - Yulita Tarigan, Devi Eka; Darmayanti, Nefi; Surbakti, Amanah (Universitas Ahmad Dahlan, 2024)
Delays in completing final assignments are common among final-year students. This research aims to examine the influence of smartphone addiction on academic procrastination through the mediator of self-regulated learning. The study uses a quantitative approach, with data collection methods involving academic procrastination scales, smartphone addiction, and self-regulated learning. The respondents in this study consisted of 304 students, selected using purposive sampling. The data were analyzed using Structural Equation Modeling (SEM) with Amos version 26. The research findings indicate that (1) there is a positive effect of smartphone addiction on academic procrastination, (2) there is a negative effect of smartphone addiction on self-regulated learning, (3) there is a negative effect of self-regulated learning on academic procrastination through the mediator of self-regulated learning, and (4) smartphone addiction influences academic procrastination through the mediator of self-regulated learning.